Win: How public entrepreneurship can transform the developing world - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2022)
This book provides a story about the Infrastructure Development Company Limited (IDCOL) written from the perspective of its first full-time Chief Executive Officer. For those who have never heard of IDCOL, it was created in 1997 by the Government of Bangladesh as a nonbank financial institution to fill the financial gap for developing medium- to large-scale infrastructure. IDCOL had a very modest start with a nominal paid-up capital of less than US$2,000, but its capital, equity, and reserves increased to US$110 million by 2020. During this massive expansion, IDCOL met various challenges. This book gives an account of these challenges and how its author has tackled them.